RURAL DEVELOPMENT IN SERBIA AND THE LOCAL COMMUNITIES - Popović, Vesna; Katić, Branko; Savić, Mirjana (Economics of Agriculture, 2011)
Rural areas encompass the most part of Serbia and they are very heterogenous in relation to natural conditions for development, production capacities, employment, infrastructure, income and standard of living. Being a bottom-up approach, rural development focuses on local actors, i.e. local agents that have an interest in the development of an identified territory. Rural development policy recognizes the necessity of capacities building for local development strategies elaboration and implementation. Recently established Rural Development Support Network (RDSN), with its regional and municipalities centers should make the RD policy more effective.